2002
DOI: 10.1038/sj.bjp.0704894
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the novel nociceptin/orphanin FQ receptor ligand, ZP120: in vitro and in vivo studies in mice

Abstract: 1 This study reports on the pharmacological characterization of ZP120, a novel ligand of the nociceptin/orphanin FQ (N/OFQ) peptide receptor, NOP. ZP120 is a structure inducing probes modi®ed NOP ligand: Zealand Pharma proprietary SIP technology was used to increase the enzymatic stability and half-life of peptide. 2 In vitro, ZP120 mimicked the inhibitory e ects of N/OFQ in the electrically stimulated mouse vas deferens, showing however higher potency (pEC 50 8.88 vs 7.74), lower maximal e ects (E max 69+5% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
34
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 21 publications
12
34
0
Order By: Relevance
“…As demonstrated by others, we found that N/OFQ is a potent inhibitor of electrically induced contractions in the MVD preparation (Berzetei-Gurske et al, 1996;Caló et al, 1996;Rizzi et al, 2002) (Fig. 1).…”
Section: In Vitro Studiessupporting
confidence: 81%
“…As demonstrated by others, we found that N/OFQ is a potent inhibitor of electrically induced contractions in the MVD preparation (Berzetei-Gurske et al, 1996;Caló et al, 1996;Rizzi et al, 2002) (Fig. 1).…”
Section: In Vitro Studiessupporting
confidence: 81%
“…Similar kinetics of action has been reported for other NOP ligands, such as the peptide ZP120 (Rizzi et al, 2002a) and the nonpeptide Ro 64-6198 (Rizzi et al, 2001b). The reason(s) for the differences in kinetic behav- Both pharmacological and knockout findings in vitro converge indicating that UFP-102 is a highly selective ligand whose effects are exclusively due to NOP receptor activation.…”
Section: Discussionsupporting
confidence: 64%
“…These effects, however, do not appear to be physiologically equivalent, motor inhibition being predominant (Marti et al, 2004a). Systemic injection of NOP receptor antagonists or deletion of the NOP receptor gene failed to affect spontaneous locomotion (Gavioli et al, 2003;Kuzmin et al, 2004;Marti et al, 2004a;Rizzi et al, 2007). In line with this view, we did not detect motor facilitation by J-113397 in the bar test (a static test), while there was a prominent effect in tests engaging the animals in repetitive and prolonged movements (i.e.…”
Section: Role Of Endogenous N/ofq In Modulation Of Locomotion Under Psupporting
confidence: 48%